Management of Surgery to Cranioplasty Reconstruction in Meningioma Patients with Hyperostosis: Case Series - Thohari, Khamim; Florensia, Rifka; Choiriyah, Nikmatul; Jamil, Ahmad Mochtar; Hardiansyah, Erwin; Abshor, Ulil (Universitas Muhammadiyah Semarang, 2025)
Background: Meningiomas, common primary brain neoplasms, become more frequent with age. They can affect osseous structures, manifesting as hyperostosis and significantly diminishing the well-being of patients. Although meningiomas' precise etiology and pathogenesis remain ambiguous, hormonal influences and other factors have been implicated in their development. This study seeks to explain surgical management and cranioplasty reconstruction to reduce recurrence and improve the well-being of patients.Objective: This case series encompasses a retrospective analysis of medical records from six patients diagnosed with meningiomas with hyperostosis, treated between December 2022 and January 2024, at Dr. Soegiri General Hospital, Lamongan. The analysis focuses on surgical interventions and cranioplasty reconstruction.Cases Presentation: Six patients had chronic cephalgia and cranial masses persisting for 3-6 years. Computed tomography imaging revealed hyperostotic changes contiguous with the neoplastic lesions, prompting craniotomy. Subsequent acrylic cranioplasty was undertaken to ensure encephalic protection and to achieve cosmetic restoration.Conclusion: For patients presenting with meningiomas and hyperostosis, symptomatic management through surgical excision and resection of the hyperostotic bone is recommended. Early implementation of cranioplasty, preferably acrylic materials, is recommended to shield cerebral structures and restore cranial morphology, given its economic feasibility and reduced infection risk compared to autologous bone grafts